Phytochemical Analysis and Antibacterial Activity of Eco-Enzyme Produced from Mixed Coffee Pulp and Pineapple Peel Waste - Atika Lestari; Norman Yoshi Haryono; Aura Berlianny; Ratna Juwita (Department of Biology Education, FSTT, Mandalika University of Education, Indonesia., 2026)
This study aimed to analyze the phytochemical content and antibacterial activity of eco-enzyme produced through the fermentation of a mixed substrate of coffee peels and pineapple peels. This study was a laboratory experiment with repeated observations, including a 2-month eco-enzyme fermentation process, assessment of color and aroma, pH measurement, phytochemical screening, and antibacterial testing against Staphylococcus aureus and Escherichia coli using the disc diffusion method. The results showed that the eco-enzyme was dark brown in color, had an acidic odor, and exhibited a pH ranging from 2.6 to 3.3. The detected phytochemical constituents included alkaloids, flavonoids, and tannins. Antibacterial testing demonstrated that the eco-enzyme derived from the mixture of coffee peels and pineapple peels exhibited activity against Staphylococcus aureus and Escherichia coli, with all three samples classified as having weak inhibitory activity. The highest inhibition zone diameter against S. aureus was observed in sample P1, measuring 5.00 ± 0.26 mm, while the highest inhibition zone against E. coli was 5.43 ± 0.78 mm. These values were still substantially lower than those of the positive control (chloramphenicol), which produced inhibition zones of 17.73 ± 2.27 mm and 21.63 ± 0.95 mm, respectively. The bacterial growth inhibition may be attributed to the presence of organic acids in the eco-enzyme, which can reduce the internal cellular pH and disrupt metabolism, as well as to the action of bioactive compounds that may inhibit DNA replication, suppress enzymatic activity, or damage cell membrane permeability. These findings indicate that antibacterial activity was detectable, although still low, highlighting the need to optimize the formulation and fermentation conditions to enhance its antibacterial potential. Nevertheless, this study contributes to the early development of natural non-clinical antibacterial agents through fermentation-based bioconversion.